Impact of Banking Fraud Awareness Booklet Among The Students of Satara - Samidha, Samidha Walvekar (Universitas Ahmad Dahlan, 2023)
With the growth of information and communication technology, the structure and nature of financial services delivery has also changed. Online banking or internet banking has emerged as a new and convenient way for using financial services like funds transfer, viewing account statement, bill payment, use of e-wallets etc. An upsurge in the use of devices connected with the internet and the convenience of online financial services has increased the risk of our hard-earned money being duped by cybercriminals. The main aim of this study is to assess the impact of Banking fraud awareness Booklet regarding online among students of Satara. The objectives of this study are to assess knowledge regarding awareness of online banking frauds among college going students, to determine the effectiveness of information booklet among college going students and also to find out association between socio-demographic variables and the booklet. The results show the significant increase in mean scores as (mean pre 16.92 SD=2.591 to mean post 18.32 SD=1.842). The paired 't' test applied showed the calculated paired t value (5.291 at 0.05 level of significance). The study reveals that there is association between, class, department & course of the subjects and level of knowledge regarding awareness on online banking frauds. The information booklet was effective in improving the knowledge of awareness regarding online banking frauds among the Undergraduate students. Keywords: Online banking frauds, Banking fraud awareness booklet.